2013
DOI: 10.1074/jbc.m113.493551
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Transforming Growth Factor β (TGFβ) Signaling in Cranial Neural Crest Cells Causes Tongue Muscle Developmental Defects

Abstract: Background: TGF␤ signaling is required in cranial neural crest (CNC) cells during tongue development. Results: TGF␤-mediated ABL1 activation in CNC cells results in altered Fgf4 and Fst gene expression and a failure of muscle development. Conclusion: TGF␤ activates the ABL1 pathway in the absence of TGF␤ receptor type II (T␤RII) during tongue development. Significance: Activation of noncanonical TGF␤ signaling causes microglossia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…Similar cases of microglossia occur in other mouse models with mesenchymal mutations, such as Wnt1-Cre; Tgfbr2 fl/fl (Hosokawa et al, 2010;Iwata et al, 2013) and Wnt1-Cre; Alk5 fl/fl (Han et al, 2014) mice. However, in those cases, changes in molecules secreted by the mesenchymal cells directly affect the tongue myogenic progenitors, resulting in altered myogenic proliferation and/or differentiation.…”
Section: Discussionsupporting
confidence: 64%
“…Similar cases of microglossia occur in other mouse models with mesenchymal mutations, such as Wnt1-Cre; Tgfbr2 fl/fl (Hosokawa et al, 2010;Iwata et al, 2013) and Wnt1-Cre; Alk5 fl/fl (Han et al, 2014) mice. However, in those cases, changes in molecules secreted by the mesenchymal cells directly affect the tongue myogenic progenitors, resulting in altered myogenic proliferation and/or differentiation.…”
Section: Discussionsupporting
confidence: 64%
“…CNC-specific Tgfbr2 mutant (Tgfbr2 fl/fl ;Wnt1-Cre) mice exhibit muscle abnormalities in the tongue (Iwata et al, 2013b) and soft palate (supplementary material Fig. S6), following defects in cell proliferation and maturation or organization.…”
Section: Research Articlementioning
confidence: 99%
“…Immunoblotting was performed as described previously (Iwata et al, 2012;Iwata et al, 2013b). Antibodies used for immunoblotting were as follows: mouse monoclonal antibodies against DKK1 (Santa Cruz Biotechnology), active form of β-catenin (ABC) and GAPDH (Millipore), and rabbit polyclonal antibody against phosphorylated β-catenin (Cell Signaling Technology).…”
Section: Immunoblotting Analysismentioning
confidence: 99%
“…Tongue primordium is comprised of mesenchyme cells derived from cranial neural crest cells (CNCCs), ectoderm-derived lingual epithelium in the distal portion and the endoderm-derived proximal portion (2). The myoblasts migrated from the occipital somites surround the CNCCs during the process of tongue development (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, the tongue muscle also exhibits unique characteristics that are distinct from those of other skeletal muscles, and different regulatory mechanisms may be in place. Previous studies demonstrated that transforming growth factor β1, Smad4 and fibroblast growth factor 6 signaling pathways regulate myogenic differentiation and myoblast fusion during tongue development (2,3). It should be noted that most previous studies focused on embryonic development of mice tongues, whereas the postnatal development of the tongue has remained to be fully explored.…”
Section: Introductionmentioning
confidence: 99%